7th Drug hypersensitivity meeting: part two. (25th August 2016) - Elera, Javier Dionicio; Boteanu, Cosmin; Blanco, Maria Aranzazu Jimenez; Gonzalez‐Mendiola, Rosario; García, Irene Carrasco; Alvarez, Antonio; Martinez, Jose Julio Laguna; Garrido, Jaume Martí; Barona, Carla Torán; Chorda, Carolina Perales; Salgueiro, Ramón López; Palacios, Miguel Díaz; et al.
Table of contents: Poster walk 11: miscellaneous drug hypersensitivity 2 (P92–P94, P96–P101) P92 16 years of experience with proton pump inhibitors (PPIs) Javier Dionicio Elera, Cosmin Boteanu, Maria Aranzazu Jimenez Blanco, Rosario Gonzalez‐Mendiola, Irene Carrasco García, Antonio Alvarez, Jose Julio Laguna Martinez P93 Allergy evaluation of quinolone induced adverse reactions Jaume Martí Garrido, Carla Torán Barona, Carolina Perales Chorda, Ramón López Salgueiro, Miguel Díaz Palacios, Dolores Hernández Fernández De Rojas P94 Bupropion‐induced acute urticaria and angioedema, a case report Emre Ali Acar, Ayse Aktas, Aylin Türel Ermertcan, Peyker Temiz P96 Delayed type hypersensitivity and study of cross‐reactivity between proton‐pump inhibitors Chien‐Yio Lin, Chung‐Yee Rosaline Hui, Ya‐Ching Chang, Chih‐Hsun Yang, Wen‐Hung Chung P97 Diagnostic work‐up in suspected hypersensitivity to proton‐pump inhibitors: looking at cross‐reactivity Fabrícia Carolino, Diana Silva, Eunice Dias De Castro, Josefina R. Cernadas P98 Management of infusion‐related hypersensitivity reactions to enzyme replacement therapy for lysosomal diseases Luis Felipe Ensina, Carolina Aranda, Ines Camelo Nunes, Alex Lacerda, Ana Maria Martins, Ekaterini Goudouris, Marcia Ribeiro, José Francisco Da Silva Franco, Leandra Queiroz, Dirceu Solé P99 Management of insulin allergy with continuous subcutaneous insulin infusion Ceyda Tunakan Dalgiç, Aytül Zerrin Sin, Fatma Düsünür Günsen, Gökten Bulut, Fatma Ömür Ardeniz, Okan Gülbahar, Emine Nihal Mete Gökmen, Ali Kokuludag P100 Off‐label use of icatibant for management of serious angioedema associated with angiotensin inhibitors Ana M. Montoro De Francisco, Talía Mª De Vicente Jiménez, Adriana M. Mendoza Parra, Angella M. Burgos Pimentel, Amelia García Luque P101 Thiocolchicoside anaphylaxis: an unusual suspect? Luis Amaral, Fabricia Carolino, Leonor Carneiro Leão, Eunice Castro, Josefina Cernadas Poster walk 12: betalactam hypersensitivity (P102–P111) P102 A curious delayed reading: a case report of a β‐lactam allergy in a child Nicole Pinto, Joana Belo, João Marques, Pedro Carreiro‐Martins, Paula Leiria‐Pinto P103 Betalactam‐induced hypersensitivity: a 10‐years' experience Amel Chaabane, Haifa Ben Romdhane, Nadia Ben Fredj, Zohra Chadly, Naceur A. Boughattas, Karim Aouam P104 Cefazolin hypersensitivity: towards optimized diagnosis Astrid P. Uyttebroek, Chris H. Bridts, Antonino Romano, Didier G. Ebo, Vito Sabato P105 Clavulanic acid allergy: two cases report Anabela Lopes, Joana Cosme, Rita Aguiar, Tatiana Lourenço, Maria‐João Paes, Amélia Spínola‐Santos, Manuel Pereira‐Barbosa P106 Diagnosis of betalactam allergy in an allergy department Cíntia Rito Cruz, Rute Pereira Dos Reis, Elza Tomaz, Ana Paula Pires, Filipe Inácio P107 Diagnostic work‐up of 410 patients with suspicion of betalactam antibiotic hypersensitivity Filipe Benito‐Garcia, Inês Mota, Magna Correia, Ângela Gaspar, Marta Chambel, Susana Piedade, Mário Morais‐Almeida P108 Immediate selective hypersensitivity reactions to clavulanic acid Alla Nakonechna, Yurij Antipkin, Tetiana Umanets, Fernando Pineda, Francisca Arribas, Volodymyr Lapshyn P109 Prevalence and incidence of penicillin hypersensitivity reactions in Colombia Pablo Andrés Miranda, Bautista De La Cruz Hoyos P110 Selective sensitization to amoxicilin and clavulanic acid Jose Julio Laguna Martinez, Aranzazu Jimenez Blanco, Javier Dionicio Elera, Cosmin Boteanu, Rosario Gonzalez‐Mendiola, Marta Del Pozo P111 Infliximab‐specific T cells are detectable also in treated patients who have not developed anti‐drug antibodies Alessandra Vultaggio, Francesca Nencini, Sara Pratesi, Andrea Matucci, Enrico Maggi Poster walk 13: biologicals, local anesthetics, others (P112–P118) P112 A case report of allergic immediate systemic reaction to adalimumab and certolizumab Ceyda Tunakan Dalgiç, Fatma Düsünür Günsen, Gökten Bulut, Fatma Ömür Ardeniz, Okan Gülbahar, Emine Nihal Mete Gökmen, Aytül Zerrin Sin, Ali Kokuludag P113 Allergy to local anesthetics: negative predictive value of skin tests Ivana Cegec, Danica Juricic Nahal, Viktorija Erdeljic Turk, Matea Radacic Aumiler, Ksenija Makar Ausperger, Iva Kraljickovic, Iveta Simic P114 Cutaneous adverse reactions of molecular targeted agents: a retrospective analysis in 150 patients in our department Yukie Yamaguchi, Tomoya Watanabe, Megumi Satoh, Tomohiko Tanegashima, Kayoko Oda, Hidefumi Wada, Michiko Aihara P115 Generalized paralysis induced by local lidocaine injection Jaechun Jason Lee, Jay Chol Choi, Hwa Young Lee P116 Hypersensitivity to local anaesthetics: a 10 year review Rosa‐Anita Rodrigues Fernandes, Emília Faria, Joana Pita, Nuno Sousa, Carmelita Ribeiro, Isabel Carrapatoso, Ana Todo Bom P117 Local anaesthetics: a rare culprit in hypersensitivity reactions Ana Rodolfo, Eunice Dias‐Castro, Josefina Cernadas P118 Stevens–Johnson syndrome in clinical practice: a variant of clinical course Marina Voronova Poster walk 14: RCM (P119–P128) P119 13 cases of severe anaphylactic reactions due to radiocontrast media Jaume Martí Garrido, Ramon Lopez Salgueiro, Diana Kury Valle, Verónica Pacheco Coronel, Carolina Perales Chordá, Dolores Hernandez Fernandez De Rojas P120 Anaphylactic shock after administration of iodinated contrast medium during cardiac catheterization Roselle Catherine Yu Madamba, Marta Ferrer, Maria Jose Goikoetxea, Carmen D'Amelio, Amalia Bernad, Olga Vega, Gabriel Gastaminza P121 Anaphylactic shock and cardiac arrest induced by gadolinium‐based contrast agents Beatriz Pola Bibián, Marina Lluncor Salazar, Gemma Vilà Nadal, Ana María Fiandor Roman, Javier Dominguez Ortega, Miguel Gonzalez Muñoz, Santiago Quirce Gancedo, Maria Rosario Cabañas Moreno P122 Anaphylaxis to gadobenate and cross‐reactivity to other gadolinium‐based contrast agents in two patients Kathrin Scherer Hofmeier P123 Anaphylaxis to glatiramer acetate in a patient with multiple sclerosis Fabrícia Carolino, Vladyslava Barzylovych, Josefina R. Cernadas P124 Delayed hypersensitivity reaction to radiocontrast media Fabrícia Carolino, Diana Silva, Leonor Leão, Josefina R. Cernadas P125 Drug reaction with eosinophilia and systemic symptoms induced by iodixanol Gemma Vilà‐Nadal, Beatriz Pola, Marina Lluncor, Ana Fiandor, Teresa Bellón, Javier Domínguez, Santiago Quirce P126 Electronic consultation support system for radiocontrast media hypersensitivity changes clinician's behavior Min‐Suk Yang, Sun‐Sin Kim, Sae‐Hoon Kim, Hye‐Ryun Kang, Heung‐Woo Park, Sang‐Heon Cho, Kyung‐Up Min, Yoon‐Seok Chang P127 Hypersensitivity reactions to iodinated contrast media: skin testing and follow‐up Danica Juricic Nahal, Ivana Cegec, Viktorija Erdeljic Turk, Iva Kraljickovic, Matea Radacic Aumiler, Ksenija Makar Ausperger, Iveta Simic P128 Would iodine allergy exist? Clémence Delahaye, Jenny Flabbee, Julie Waton, Olivia Bauvin, Annick Barbaud Poster walk 15: MPE/type 4 (P129–P137) P129 Delayed hypersensitivity cutaneous reactions: a case/control study from a tunisian database Karim Aouam, Najah Ben Fadhel, Zohra Chadly, Nadia Ben Fredj, Naceur A. Boughattas, Amel Chaabane P130 Delayed hypersensitivity reactions to cephalosporins: a review of seven cases Joana Cosme, Anabela Lopes, Amélia Spínola‐Santos, Manuel Pereira‐Barbosa P131 Diclofenac induced allergic contact dermatitis: case series of four patients Sandra Jerkovic Gulin, Anca Chiriac P132 Late‐onset maculopapular rash to irbesartan Bárbara Kong Cardoso, Elza Tomaz, Regina Viseu, Filipe Inácio P133 Nonimmediate hypersensitivity reactions to betalactams: a retrospective analysis Ana Moreira, Susana Cadinha, Ana Castro Neves, Patricia Barreira, Daniela Malheiro, J. P. Moreira Da Silva P134 Occupational airborne contact dermatitis to omeprazole Ružica Jurakic‐Toncic, Suzana Ljubojevic, Petra Turcic P135 Ornidazole‐induced fixed drug eruption confirmed by positive patch test on a residual pigmented lesion Liesbeth Gilissen, Sara Huygens, An Goossens P136 Repeated delayed reaction induced by amoxicillin and amoxicillin clavulanate Inmaculada Andreu, Ramon Lopez‐Salgueiro, Alicia Martinez Romero, Pau Gomez Cabezas P137 Systemic photosensitivity from fenofibrate in a patient photo‐sensitized to ketoprofen Liesbeth Gilissen, An Goossens Poster walk 16: HLA genetics (P138–P146) P138 A copy number variation in ALOX5 and PTGER1 is associated with nonsteroidal anti‐inflammatory drugs induced urticaria and/or angioedema Pedro Ayuso Parejo, Maria Del Carmen Plaza‐Serón, Inmaculada Doña, Natalia Blanca López, Carlos Flores, Luisa Galindo, Ana Molina, James Richard Perkins, Jose Antonio Cornejo‐García, José Augusto García‐Agúndez, Elena García‐Martín, Paloma Campo, María Gabriela Canto, Miguel Blanca P139 Association of galectin‐3 (LGALS3) single nucleotide polymorphisms with non‐steroidal anti‐inflammatory drugs‐induced urticaria/angioedema José Antonio Cornejo‐Garcia, Inmaculada Doña, Rosa María Guéant‐Rodríguez, Natalia Blanca‐López, María Carmen Plaza‐Serón, Raquel Jurado‐Escobar, Esther Barrionuevo, María Salas, María Luisa Galindo, Gabriela Canto, Miguel Blanca, Jean‐Louis Guéant P140 Detection of T cell responses to ticlopidine using peripheral blood mononuclear cells from HLA‐A*33:03+ healthy donors Toru Usui, Arun Tailor, Lee Faulkner, John Farrell, Ana Alfirevic, B. Kevin Park, Dean J. Naisbitt P141 Epistasis approaches to identify novel genes potentially involved in NSAIDs hypersensitivity James Richard Perkins, Jose Antonio Cornejo García, Oswaldo Trelles, Inmaculada Doña, Esther Barrionuevo, María Salas, María Auxiliadora Guerrero, Miguel Blanca, Alex Upton P142 Genetic predisposition of cold medicine related SJS/TEN with severe ocular complications Mayumi Ueta, Hiromi Sawai, Chie Sotozono, Katushi Tokunaga, Shigeru Kinoshita P143 HLA‐B*13:01 and dapsone induced hypersensitivity in Thai population Chonlaphat Chonlaphat Sukasem, Patompong Satapornpong, Therdpong Tempark, Pawinee Rerknimitr, Kulprapat Pairayayutakul, Jettanong Klaewsongkram P144 HLA‐B*15:02 alleles and lamotrigine‐induced cutaneous adverse drug reactions in Thai Chonlaphat Sukasem, N. Koomdee, T. Jantararoungtong, S. Santon, A. Puangpetch, U. Intusoma, W. Tassaneeyakul, V. Theeramoke P145 HLA‐B*38:01 and HLA‐A*24:02 allele frequencies in Spanish patients with lamotrigine‐induced SCARs Teresa Bellón, Elena Ramirez, Alberto Manuel Borobia, Hoi Tong, Jose Luis Castañer, Francisco José De Abajo P146 Overrepresentation of a class II HLA haplotype in severe hypersensitivity type I reactions to carboplatin Violeta Régnier Galvao, Rebecca Pavlos, Elizabeth Mckinnon, Kristina Williams, Alicia Beeghly‐Fadiel, Alec Redwood, Elizabeth Phillips, Mariana Castells Poster walk 17: in vivo diagnosis + sIgE (P147–P154) P147 Absence of specific Ig‐e against beta‐lactams 9 months after an allergic reaction to amoxicillin‐clavulanic acid Elisa Boni, Marina Russello, Marina Mauro P148 Drug provocation tests in suspected opioid allergy Kok Loong Ue, Krzysztof Rutkowski P149 Improvement to the specific IgE cut‐off in the assess of β‐lactamic allergy Victor Soriano Gomis, Jorge Frances Ferre, Angel Esteban Rodriguez, Vicente Cantó Reig, Javier Fernandez Sanchez P150 Initial false negative specific IgE to gelatin in a patient with gelatin‐induced anaphylaxis Christine Breynaert, Erna Van Hoeyveld, Rik Schrijvers P151 Inmediate reactions to beta‐lactam antibiotics: pattern of skin test response over the time Jose Julio Laguna Martinez, Rosario Gonzalez Mendiola, Javier Dionicio Elera, Cosmin Boteanu, Aranzazu Jimenez Blanco, Marta Del Pozo, Raquel Fuentes Irigoyen P152 New fluorescent dendrimeric antigens for the evaluation of dendritic cell maturation as a test to detect allergy reactions to amoxicillin Daniel Collado, Yolanda Vida, Francisco Najera, Ezequiel Perez‐Inestrosa, Pablo Mesa‐Antunez, Cristobalina Mayorga, María José Torres, Miguel Blanca P153 Positive skin test or positive specific IgE to penicillin does not predict penicillin allergy Line K. Tannert, Charlotte G. Mortz, Per Stahl Skov, Carsten Bindslev‐Jensen P154 Significance of skin testing and in vitro‐analysis of neuromuscular blocking agents in diagnosis of perioperative drug hypersensitivity: evaluation of a negative control population Wolfgang Pfützner, Hannah Dörnbach, Johanna Visse, Michele Rauber, Christian Möbs Poster walk 18: in vitro/ex vivo (P155–P158, P160–P164) P155 Diagnostic value of the lymphocyte toxicity assay (LTA) and the in vitro platelet toxicity assay (IPTA) for β‐lactam allergy Abdelbaset A. Elzagallaai, Lindsey Chow, Awatif M. Abuzgaia, Michael J. Rieder P156 Enzyme linked immunospot assay used in the diagnosis of severe cutaneous adverse reactions to antimicrobials Alec Redwood, Jason Trubiano, Rebecca Pavlos, Emily Woolnough, Kaija Stautins, Christina Cheng, Elizabeth Phillips P157 Evaluation of in vitro diagnostic methods for identifying the culprit drugs in drug hypersensitivity Kenichi Kato, Hiroaki Azukizawa, Takaaki Hanafusa, Ichiro Katayama P158 Ex‐vivo expanded skin‐infiltrating T cells from severe drug eruptions are reactive with causative drugs: a possible novel method for determination of causative drugs Toshiharu Fujiyama, Hideo Hashizume, Takatsune Umayahara, Taisuke Ito, Yoshiki Tokura P160 In vitro release of IL‐2, IL‐5 and IL‐13 in diagnosis of patients with delayed‐type nickel hypersensitivity Mira Silar, Mihaela Zidarn, Helena Rupnik, Peter Korosec P161 Single cell analysis of drug responsive T cells; identification of candidate drug reactive T cell receptors in abacavir and carbamazepine hypersensitivity Alec James Redwood, Kaija Strautins, Katie White, Abha Chopra, Katherine Konvinse, Shay Leary, Rebecca Pavlos, Simon Mallal, Elizabeth Phillips P162 Specificity and sensitivity of LTT in DRESS: analysis of agreement with the Spanish pharmacovigilance system probability algorithm Rosario Cabañas, Elena Ramirez, Ana María Fiandor, Teresa Bellón P163 The role of interleukin‐22 in β‐lactam hypersensitivity Andrew Sullivan, Paul Whitaker, Daniel Peckham, B. Kevin Park, Dean J. Naisbitt P164 Vancomycin‐specific T cell responses and teicoplanin cross‐reactivity Wei Yann Haw, Marta E. Polak, Carolann Mcguire, Michael R. Ardern‐Jones Poster walk 19: BAT and biomarkers (P165–P173) P165 A combination of early biomarkers useful for the prediction of severe ADRs Yumi Aoyama, Tetsuo Shiohara P166 Basophil activation test in the diagnostic approach of reactions during general anaesthesia Ana Moreira, Susana Cadinha, Patrícia Barreira, Ana Castro Neves, Daniela Malheiro, Sara Correia, J. P. Moreira Da Silva P167 IL‐10 can be related to successful desensitization Asli Gelincik, Semra Demir, Fatma Sen, Hamza Ugur Bozbey, Muge Olgac, Derya Unal, Raif Coskun, Bahauddin Colakoglu, Suna Buyuozturk, Esin Çatin‐Aktas, Gunnur Deniz P168 Immediate reactions to proton pump inhibitors: value of basophil activation test Maria Salas, Jose Julio Laguna, Esther Barrionuevo, J. Dionicio, Tahia Fernandez, R. Gonzalez‐Mendiola, I. Olazabal, Maria Dolores Ruiz, Miguel Blanca, Cristobalina Mayorga, Maria José Torres P169 Improvement of the elevated tryptase criterion to discriminate IgE from non‐IgE mediated allergic reactions Gabriel Gastaminza, Alberto Lafuente, Carmen D'Amelio, Amalia Bernad, Olga Vega, Roselle Catherine Madamba, M. Jose Goikoetxea, Marta Ferrer, Jorge Núñez P170 Low expression of Tim‐3 could serve as a biomarker for control and diagnose maculopapular exanthema induced by drugs Tahia Diana Fernández, Inmaculada Doña, Francisca Palomares, Rubén Fernández, Maria Salas, Esther Barrionuevo, Maria Isabel Sanchez, Miguel Blanca, Maria José Torres, Cristobalina Mayorga P171 Role of basophil activation test using two different activation markers for the diagnosis of allergy to fluoroquinolones Esther Barrionuevo, Tahía Fernandez, Arturo Ruiz, Adriana Ariza, Maria Salas, Inmaculada Doña, Ana Molina, Miguel Blanca, Maria Jose Torres, Cristobalina Mayorga P172 The importance of basophil activation test in anaphylaxis due to celecoxib Amalia Bernad Alonso, Carmen D'Amelio Garófalo, Olga Vega Matute, Marta Ferrer Puga, María José Goikoetxea Lapresa, Roselle Catherine Yu Madamba, Gabriel Gastaminza Lasarte P173 The role of basophil activation test in the diagnosis of immediate type drug hypersensitivity to betalactam antibiotics Antonia Thinnes, Hans F. Merk, Jens Malte Baron, Martin Leverkus, Galina Balakirski Poster walk 20: TCR recognition, cellular (P174–P183) P174 Characterisation of the effect of co‐inhibitory signalling on the activation of drug‐derived antigen‐specific T‐cells Andrew Gibson, Monday Ogese, Lee Faulkner, B. Kevin Park, Dean J. Naisbitt P175 Characterization of drug hapten‐specific T cell responses in piperacillin hypersensitive patients Zaid Al‐Attar, Fiazia Yaseen, Xiaoli Meng, Rozalind Jenkins, Paul Whitaker, Daniel Peckham, Lee Faulkner, John Farrel, Kevin Park, Dean Naisbitt P176 Characterization of the response of T‐cells to telaprevir and its metabolite in normal volunteers Zaid Al‐Attar, Khetam Alhilali, Yanni Xue, John Farrell, Lee Faulkner, Kevin Park, Dean Naisbitt P177 Characterization of the T cell receptor signatures of drug‐responsive T cells Patricia Illing, Nicole Mifsud, Heidi Fettke, Jeffrey Lai, Rebecca Ho, Patrick Kwan, Anthony Purcell P178 Defining the signals between hepatocytes and immune cells in idiosyncratic drug‐induced liver injury (DILI) Monday O. Ogese, Lee Faulkner, B. Kevin Park, Catherine Betts, Dean J. Naisbitt P179 Development of novel chemicals that do not bind to HLA‐B*57:01 or activate CD8 + T‐cells through modification of the 6‐amino cyclopropyl group of abacavir Paul Thomson, John Farrell, Mohammad Alhaidari, Neill Berry, Paul M. O'Neill, B. Kevin Park, Dean J. Naisbitt P180 Generation and characterization of dapsone‐ and nitroso‐dapsone‐specific T‐cell clones using lymphocytes from healthy volunteers Abdulaziz Alzahrani, Monday O. Ogese, John Farrell, Lee Faulkner, Andrew Gibson, Arun Tailor, B. Kevin Park, Dean J. Naisbitt P181 Identification of benzylpenicillin‐hapten peptides responsible for naïve T‐cell activation and immunization of allergic patients to penicillin Marie Eliane Azoury, Lucia Fili, Rami Bechara, Noémie Scornet, Cathy Nhim, Richard Weaver, Nancy Claude, Delphine Joseph, Bernard Maillere, Paola Parronchi, Marc Pallardy P182 Massive expansion of clonotypic and polycytotoxic CD8+ T cells in toxic epidermal necrolysis Axel Patrice Villani, Aurore Rozières, Benoît Bensaïd, Mathilde Tardieu, Floriane Albert, Virginie Mutez, Tugba Baysal, Marc Pallardy, Janet Maryanski, Jean‐François Nicolas, Osami Kanagawa, Marc Vocanson P183 Pharmaco‐immunological synapse of HLA‐drug‐TCR in SCAR Shuen‐Iu Hung Poster walk 21: new in vitro methods, haptens, etc. (P184–P194) P184 Amoxicillin‐clavulanate forms distinct multiple haptenic structures on human serum albumin in patients Xiaoli Meng, Arun Tailor, Caroline J. Harrison, Rosalind E. Jenkins, Paul Whitaker, Neil S. French, Dean J. Naisbitt, B. Kevin Park P185 Dendrimeric antigens for studying the influence of penicillin determinants orientation on IgE recognition Maria Isabel Montañez, Cristobalina Mayorga, Francisco Najera, Adriana Ariza, Tahia D. Fernandez, Maria Salas, Angela Martin‐Serrano, Miguel Blanca, Ezequiel Perez‐Inestrosa, Maria Jose Torres P186 Dendrimeric antigens on solid supports: designed materials for IgE quantification Yolanda Vida, Maria Isabel Montañez, Noemi Molina, Daniel Collado, Francisco Najera, Adriana Ariza, Maria Jose Torres, Cristobalina Mayorga, Ezequiel Perez‐Inestrosa P187 Development of a screening assay for drug hypersensitivity using naïve T cells from donors with seven different HLA class I risk alleles Lee Faulkner, Sally Wood, Ana Alfirevic, Munir Pirmohamed, Dean J. Naisbitt, B. Kevin Park P188 Different patterns of recognition of structures derived from amoxicillin by IgE antibodies from patients with immediate hypersensitivity reactions to betalactams Adriana Ariza, Cristobalina Mayorga, María Isabel Montañez, María Salas, Inmaculada Doña, Ángela Martín‐Serrano, Ezequiel Pérez‐Inestrosa, Dolores Pérez‐Sala, Miguel Blanca, Antonio E. Guzmán, María José Torres P189 High‐resolution typing of HLA polymorphism and T‐cell receptor repertoire for severe adverse drug reactions based on the cost‐effective next‐generation sequencing approaches Tai‐Ming Ko, Yuan‐Tsong Chen, Jer‐Yuarn Wu P190 Identification and fate of intracellular proteins haptenated by amoxicillin Francisco J. Sánchez‐Gómez, Juan M. González‐Morena, Yolanda Vida, Ezequiel Pérez‐Inestrosa, Miguel Blanca, María J. Torres, Dolores Pérez‐Sala P191 In vitro detection of terbinafine protein adducts Arun Tailor, Toru Usui, Yanni Xue, Xiaoli Meng, Dean J. Naisbitt, B. Kevin Park P192 MicroRNAs dysregulation in PBMCs from drug hypersensitivity patients during drug challenge in vitro Alejandra Monroy Arreola, Jesus Agustin Badillo Corona, Silvia Mendez Flores, Judith Dominguez Cherit, Dean J. Naisbitt, Noe Valentin Duran Figueroa, Jose Luis Castrejon Flores P193 NSAIDs‐exacerbated cutaneous disease: high throughput gene expression profiling José Antonio Cornejo‐García, James Perkins, Natalia Blanca‐López, Diana Pérez‐Alzate, Raquel Jurado‐Escobar, Inmaculada Doña, Gador Bogas, María J. Torres, Gabriela Canto, Miguel Blanca P194 Utility of skin tests in non‐immediate reactions to amoxicillin Luis Mario Tubella Marti, Fernando Pineda De La Losa, Francisca Arribas Poves, Jaime Tubella Lopez, Teodora Lopez Santiago